2013
DOI: 10.1128/aac.02316-12
|View full text |Cite
|
Sign up to set email alerts
|

Solithromycin Inhibition of Protein Synthesis and Ribosome Biogenesis in Staphylococcus aureus, Streptococcus pneumoniae, and Haemophilus influenzae

Abstract: The continuing increase in antibiotic-resistant microorganisms is driving the search for new antibiotic targets and improved antimicrobial agents. Ketolides are semisynthetic derivatives of macrolide antibiotics, which are effective against certain resistant organisms. Solithromycin (CEM-101) is a novel fluoroketolide with improved antimicrobial effectiveness. This compound binds to the large 50S subunit of the ribosome and inhibits protein biosynthesis. Like other ketolides, it should impair bacterial ribosom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(23 citation statements)
references
References 25 publications
(58 reference statements)
0
23
0
Order By: Relevance
“…Solithromycin (CEM-101; Cempra) (Fig. 3, compound 5) is a novel fluoroketolide that binds to the 50S ribosomal subunit with an affinity similar to that of telithromycin (83). The antimicrobial activity of solithromycin is directed against respiratory pathogens, with 99.9% of its MICs being Յ0.5 g/ml against the streptococci and with MIC 90 values of 2 g/ml and 0.12 g/ml against Haemophilus influenzae and Moraxella catarrhalis, respectively (84).…”
Section: Ketolidesmentioning
confidence: 99%
“…Solithromycin (CEM-101; Cempra) (Fig. 3, compound 5) is a novel fluoroketolide that binds to the 50S ribosomal subunit with an affinity similar to that of telithromycin (83). The antimicrobial activity of solithromycin is directed against respiratory pathogens, with 99.9% of its MICs being Յ0.5 g/ml against the streptococci and with MIC 90 values of 2 g/ml and 0.12 g/ml against Haemophilus influenzae and Moraxella catarrhalis, respectively (84).…”
Section: Ketolidesmentioning
confidence: 99%
“…It binds to the large 50S subunit of the ribosome and inhibits protein biosynthesis, presumably preventing ribosomal subunit formation (16). Rodgers and colleagues reported that solithromy- cin inhibits ribosomal biosynthesis of S. pneumoniae and NTHi at nanogram concentrations, albeit S. pneumoniae was nearly 20-fold more sensitive to its action than to that of NTHi.…”
Section: Discussionmentioning
confidence: 99%
“…Not only is it extremely effective against Mollicutes (Ureaplasma and Mycoplasma spp. ), the organisms most commonly isolated from amniotic fluid following preterm labor or PPROM, but it is also highly effective against other important genital tract pathogens, such as group B streptococci, N. gonorrhoeae, and C. trachomatis (32,(34)(35)(36)(37)(38)(39)(40). Assuming that the present findings can be replicated in human pregnancy, then administration of solithromycin to women in preterm labor or PPROM would be expected to constitute a markedly more effective antenatal antimicrobial therapy than currently used macrolides, with commensurate benefits in the reduction of neonatal infections and associated morbidity and mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Solithromycin (CEM-101) is a novel macrolide/fluoroketolide antibiotic which exhibits broad-spectrum activity against Grampositive and some Gram-negative organisms, including Neisseria gonorrhoeae, Chlamydia trachomatis, Haemophilus spp., streptococci, and enterococci (31)(32)(33)(34)(35)(36)(37). It is exceptionally potent against Ureaplasma parvum, Ureaplasma urealyticum, and Mycoplasma hominis (125 to 250 times more potent than azithromycin) (31).…”
mentioning
confidence: 99%